Development of Pesantren Curriculum in Improving the Quality of Education (Case Study at Al-Ittihad Islamic Boarding School, Poncol, Al-Huda Islamic Boarding School, Petak, Semarang Regency) - Martono Martono (Syntax Idea)
Microsoft Office Translator This study aims to analyze the process of developing the yellow book curriculum of pesantren in improving the quality of education at Al-Ittihad Poncol Islamic Boarding School, Al-Huda Islamic Boarding School Petak Semarang Regency. To analyze the implications of developing the yellow book curriculum in improving the quality of education in the Al-Ittihad Poncol Islamic Boarding School in Semarang Regency and the Al-Huda Islamic Boarding School in Semarang Regency, to analyze the reasons why the yellow book curriculum needs to be applied in the Islamic boarding school environment in Indonesia. This research uses a qualitative approach with natural characteristics (Natural Setting) as a source of direct, descriptive data, process is more important than results. Primary data of caregivers, heads of Islamic boarding schools, chairmen and representatives of the curriculum, ustadz, and Santri sons / daughters of Al-Ittihad Poncol Islamic boarding school and Al-Huda Petak Islamic boarding school. Data collection techniques with in-depth interviews, observation and documentation. Data analysis uses descriptive analysis methods, content analysis and critical analysis. The Discussion Method uses, inductive method, deductive method and comparative method. The results of this study are a) The history of al-Ittihad Islamic Boarding School and al-Huda Islamic Boarding School developed from Sufism Islamic boarding schools, studying the Qur'an and studying the yellow book using the classical system, b) The development process of Islamic boarding schools Pesantren al-Ittihad and Pesantren al-Huda through planning, organizing, implementing and controlling, in accordance with existing theories, c) Implications of Pesantren al-Ittihad and Pesantren al-Huda in their development on quality Education has two aspects, namely: Characteristics of quality Pesantren Education and curriculum development, d) The Yellow Book curriculum must still be applied in Islamic boarding schools in Indonesia: a) The yellow book has been tested for hundreds of years. b) The Yellow Book is still authentic (preserved authenticity), c) Ease of access, d) memorization, accuracy and a lot of practice.